Kronika naší rodiny" vojvodovské Češky Ester Karbulové - Jakoubek, Marek (Lidé města, 2011)
This edition presents a commented transcription of the memoirs of Ester Karbulová, a former inhabitant of the only Czech village in Bulgaria - Vojvodovo. The memoirs cover many aspects of the (ex)Vojvodovo villager's life in Bulgaria as well as in South Moravia, where almost all Vojvodovan Czechs settled after their remigration following World War II. The edition is supplemented by informative commentaries and prefaced by a short introduction explaining the background of the manuscript in the context of history of Vojvodovo and its Czech (ex)inhabitants. A brief review of other manuscripts written by Vojvodovo (ex)villagers, as well as of existing academic literature concerning Vojvodovo is also presented.